Single crystal type lithium-rich manganese-based positive electrode material and preparation method thereof, lithium ion battery positive plate and lithium ion battery
By preparing the positive electrode material of the lithium ion battery, the two sintering methods are used to control the lithium source and the Moore of the front -drive body, and the synthesis problem of the single crystal lithium -rich positive pole material is solved, and the single crystal type of large particle size is achieved. Material preparation improves the volume ratio and cycle stability of the battery.
Patent Information
- Application Number
- CN202411509384.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult to synthesize a single crystal lithium-rich manganese-based positive electrode material with larger particle sizes, and it is easy to increase the degree of Li+/Ni2+ mixed displacement in the material during the synthesis process, reducing electrochemical performance.
By sintering the first part of the lithium source with the diverse front drive of nickel -containing nickel -containing, the intermediate of the spinel structure is obtained, and the second part of the lithium source and the intermediate sintering will be formed to form a single crystal rich rich rich. Lithium manganese base positive pole material. This method By controlling the Moorbi of the lithium source and the front -wheel drive, the first sintering is performed when the lithium source is insufficient, so as to obtain a large particle size intermediate, and help synthesize the single -crystal LMR positive pole material with large particles size.
A single crystal -rich lithium -rich manganese base material with a larger granules is achieved, which improves the structural stability, volume capacity and cycle stability of the material, and the preparation method is simple and safe, the cost is suitable, and it is suitable for mass production.
Smart Images

Figure CN119370913A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a single crystal lithium-rich manganese-based positive electrode material and a preparation method thereof, a lithium-ion battery positive electrode sheet and a lithium-ion battery. Background Art
[0002] Polymorphic lithium-manganese-rich layered cathode materials (LMR) are considered to be strong candidates for the next generation of high-energy lithium-ion battery cathode materials due to their high discharge capacity (>260mAh / g). However, there are many intrinsic defects in lithium-manganese-rich cathode materials, which limit their widespread commercial application. These defects include but are not limited to: low unit cell density due to the presence of Li2MnO3 phase, which reduces the volume energy density; poor kinetic performance; severe pressure drop effect caused by the phase transition from layered phase to spinel phase; and the generation of microcracks between crystals. In contrast, single-crystal (SC) LMR cathode materials have attracted widespread attention due to their unique morphology. Single-crystal materials are composed of dispersed micron-sized primary particles, which greatly reduces the specific surface area of LMR materials and helps to inhibit the infiltration of electrolyte into the bulk phase of the material, thereby slowing down the electrochemical performance degradation of the material. In addition, the dispersed primary particles effectively alleviate the anisotropic volume deformation between agglomerated polycrystalline particles and reduce the risk of microcracks; the reduction in specific surface area and the reduction in ineffective pores between particles also significantly increase the compaction density of the material, thereby improving the volume energy density of the LMR material.
[0003] However, unlike the single-crystal high-nickel cathode materials that have been successfully commercialized, the biggest problem facing single-crystal LMR materials is the difficulty in synthesis. Since the bond energy of Mn-O is much higher than that of Ni / Co-O, and there are more Mn-O bonds in LMR materials, it is difficult to synthesize single-crystal morphology. It is difficult to promote grain growth by simply increasing the calcination temperature or extending the high-temperature calcination time. Therefore, it is difficult to synthesize single-crystal morphology LMR materials with larger particle sizes. Single-crystal particles with smaller particle sizes lose the significance of their unique morphology and it is difficult to achieve good electrochemical stability. At the same time, this increased calcination temperature or extended high-temperature calcination time will increase the Li content in the material. + / Ni 2+ The degree of mixing further reduces the electrochemical performance of the material. In addition, although the introduction of molten salt can successfully synthesize single-crystal LMR materials with a good degree of dispersion, the required amount of molten salt is too large, making it difficult to obtain industrial applications, and it also faces challenges in terms of cost and environmental protection. Summary of the invention
[0004] The purpose of the present invention is to overcome the problem that it is difficult to synthesize a single crystal lithium-rich manganese-based positive electrode material with a larger particle size in the prior art, and to provide a single crystal lithium-rich manganese-based positive electrode material and a preparation method thereof, a lithium-ion battery positive electrode sheet and a lithium-ion battery. The single crystal lithium-rich manganese-based positive electrode material provided by the present invention has larger primary particles.
[0005] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a single crystal lithium-rich manganese-based positive electrode material, wherein the preparation method comprises:
[0006] Sintering the first part of the lithium source and the nickel-manganese-containing multinary precursor for the first time to obtain an intermediate with a spinel structure, wherein the molar ratio of the first part of the lithium source to the nickel-manganese-containing multinary precursor is 0.2-1:1;
[0007] Sintering the second portion of the lithium source and the spinel structure intermediate for a second time to obtain a single-crystal lithium-rich manganese-based positive electrode material, wherein the molar ratio of the second portion of the lithium source to the spinel structure intermediate is 0.5-1.4:1;
[0008] The molar ratio of the total amount of the first lithium source and the second lithium source to the nickel-manganese-containing multi-element precursor is greater than 1.25.
[0009] The second aspect of the present invention provides a single crystal lithium-rich manganese-based positive electrode material prepared according to the preparation method described in the first aspect of the present invention, wherein the single crystal lithium-rich manganese-based positive electrode material includes a layered phase and a lithium-rich phase, and the single crystal lithium-rich manganese-based positive electrode material includes a plurality of primary particles with an average particle size of 2.5-3 microns.
[0010] A third aspect of the present invention is a positive electrode sheet for a lithium-ion battery, wherein the positive electrode sheet for a lithium-ion battery comprises the single-crystal lithium-rich manganese-based positive electrode material described in the second aspect of the present invention.
[0011] A fourth aspect of the present invention is a lithium ion battery, wherein the lithium ion battery comprises the lithium ion battery positive electrode sheet described in the third aspect of the present invention.
[0012] Through the above technical solution, the technical solution provided by the present invention achieves the following beneficial effects:
[0013] (1) The positive electrode material provided by the present invention contains a layered phase and a lithium-rich phase, including a plurality of dispersed primary particles, and the size of the primary particles is relatively large, so that the positive electrode material has excellent structural stability and no cracks in the crystal. The lithium-ion battery made from the positive electrode material has excellent volumetric capacity and cycle stability.
[0014] (2) The preparation method of the positive electrode material provided by the present invention controls the molar ratio of the lithium source to the precursor to perform the first sintering under the condition of insufficient lithium source, thereby obtaining an intermediate with a spinel structure having a large particle size, and synthesizing a single-crystal LMR positive electrode material with the help of the intermediate, thereby greatly improving the primary particle size of the obtained positive electrode material, and further improving the performance of the positive electrode material. The preparation method is simple and safe, low in cost, and has good continuity, and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is the SEM image of the positive electrode materials prepared in Example 1 and Comparative Example 1 and Comparative Example 2;
[0016] Figure 2 is the SEM image of the intermediates prepared in Example 1 and Comparative Examples 7-11;
[0017] Figure 3 is the XRD diagram of the positive electrode materials prepared in Example 1 and Comparative Example 1 and Comparative Example 2;
[0018] Figure 4 is the Raman spectra of the intermediate and the positive electrode material obtained in Example 1;
[0019] Figure 5 It is a first-week weight specific capacity curve of the positive electrode materials prepared in Example 1, Comparative Example 1 and Comparative Example 2;
[0020] Figure 6 1 is a first-week volume specific capacity curve of the positive electrode materials prepared in Example 1, Comparative Example 1 and Comparative Example 2;
[0021] Figure 7 1 is a graph of the 100-cycle discharge weight specific capacity retention rate of the positive electrode materials prepared in Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise specified, "plurality" means two or more.
[0024] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0025] A first aspect of the present invention provides a method for preparing a single-crystal lithium-rich manganese-based positive electrode material, wherein the preparation method comprises:
[0026] Sintering the first part of the lithium source and the nickel-manganese-containing multinary precursor for the first time to obtain an intermediate with a spinel structure, wherein the molar ratio of the first part of the lithium source to the nickel-manganese-containing multinary precursor is 0.2-1:1;
[0027] Sintering the second portion of the lithium source and the spinel structure intermediate for a second time to obtain a single-crystal lithium-rich manganese-based positive electrode material, wherein the molar ratio of the second portion of the lithium source to the spinel structure intermediate is 0.5-1.4:1;
[0028] The molar ratio of the total amount of the first lithium source and the second lithium source to the nickel-manganese-containing multi-element precursor is greater than 1.25.
[0029] The present invention performs a first sintering of a lithium source and a nickel-manganese-containing multinary precursor under the condition of insufficient lithium source to form an intermediate with a spinel structure having a larger particle size, and then further adds a lithium source to perform a second sintering of the lithium source and the intermediate with the spinel structure to form a layered phase layer. By using the intermediate with a larger particle size, the primary particle size of the prepared positive electrode material is increased, thereby improving the volume specific capacity and cycle stability of the obtained positive electrode material.
[0030] The molar ratio of the first part of the lithium source to the nickel-manganese-containing multi-component precursor can be any value between any two of 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, and 1:1; the molar ratio of the second part of the lithium source to the spinel structure intermediate can be any value between any two of 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, and 1.4:1; the molar ratio of the total amount of the first part of the lithium source and the second part of the lithium source to the nickel-manganese-containing multi-component precursor is greater than 1.25, for example, it can be 1.3, 1.4, 1.5, 1.6, 1.7, etc.
[0031] In some embodiments, preferably, the first sintering process includes: heating from room temperature to 500-650°C at a heating rate of 3-7°C / min, pre-sintering for 2-8h, and then heating to 880-980°C at a heating rate of 3-7°C / min, and sintering for 2-8h.
[0032] In some embodiments, preferably, the first sintering process includes: heating from room temperature to 550-620°C at a heating rate of 4-6°C / min, pre-sintering for 3-7h, then heating to 920-950°C at a heating rate of 4-6°C / min, and sintering for 4-6h.
[0033] During the first sintering process, pre-sintering is beneficial to the decomposition of the lithium source, so that it can better combine with the precursor and prepare for the subsequent formal sintering to form the required intermediate. The heating rate is related to whether a rock salt phase will be formed. The preferred heating rate of the present invention basically does not form a rock salt phase, which is more conducive to improving the electrochemical performance of the obtained positive electrode material. The heating rates of pre-sintering and sintering can be any value between any two of 3°C / min, 4°C / min, 5°C / min, 6°C / min, and 7°C / min, respectively and independently; the pre-sintering temperature can be any value between any two of 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, and 650°C; the pre-sintering time can be any value between any two of 2h, 3h, 4h, 5h, 6h, 7h, and 8h; the sintering temperature can be any value between any two of 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, 970°C, and 980°C; and the sintering time can be any value between any two of 2h, 3h, 4h, 5h, 6h, 7h, and 8h.
[0034] In some embodiments, preferably, the second sintering process includes: heating from room temperature to 500-650°C at a heating rate of 3-7°C / min, pre-sintering for 2-8h, then heating to 880-980°C at a heating rate of 3-7°C / min, and sintering for 8-15h.
[0035] In some embodiments, preferably, the second sintering process includes: heating from room temperature to 550-620°C at a heating rate of 4-6°C / min, pre-sintering for 3-7h, then heating to 920-950°C at a heating rate of 4-6°C / min, and sintering for 10-14h.
[0036] According to the present invention, the room temperature is 25-35°C.
[0037] During the second sintering process, pre-sintering is beneficial to the decomposition of the lithium source, so that it can better combine with the intermediate and prepare for the subsequent formal sintering to form the required negative electrode material. During the second sintering process, the heating rates of pre-sintering and sintering can be any values between any two of 3°C / min, 4°C / min, 5°C / min, 6°C / min, and 7°C / min, respectively and independently; the pre-sintering temperature can be any value between any two of 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, and 650°C; the pre-sintering time can be any value between any two of 8h, 9h, 10h, 11h, 12h, 13h, 14h, and 15h; the sintering temperature can be any value between any two of 920°C, 930°C, 940°C, 950°C, 960°C, 970°C, and 980°C; and the sintering time can be any value between any two of 10h, 11h, 12h, 13h, and 14h.
[0038] In some embodiments, preferably, the lithium source is selected from LiOH and / or Li2CO3.
[0039] In some embodiments, preferably, the general formula of the nickel-manganese-containing multi-element precursor is: Ni x Co y Mn z (OH)2, where 0.15≤x≤0.3, 0≤y≤0.2, 0.5≤z≤0.8.
[0040] In some embodiments, preferably, the nickel-manganese-containing multi-element precursor is selected from Ni 0.25 Mn 0.75 (OH)2、Ni 0.2 Co 0.1 Mn 0.7 (OH)2 and Ni 0.1625 Co0.1625 Mn 0.675 There are many choices of multi-element precursors containing nickel and manganese, and when the selected precursor contains Co, it is beneficial to further improve the electrochemical performance.
[0041] In some embodiments, preferably, the preparation method further comprises: uniformly mixing the first part of the lithium source with the nickel-manganese-containing multinary precursor and then performing the first calcination, and uniformly mixing the second part of the lithium source with the spinel structure intermediate and then performing the second sintering. The conditions for the two mixings include: a rotation speed of 1300-1700rpm, preferably 1300-1700rpm, and a time of 3-7min, preferably 4-6min.
[0042] The second aspect of the present invention provides a single crystal lithium-rich manganese-based positive electrode material prepared according to the preparation method described in the first aspect of the present invention, wherein the single crystal lithium-rich manganese-based positive electrode material includes a layered phase and a lithium-rich phase, and the single crystal lithium-rich manganese-based positive electrode material includes primary particles with an average particle size of 1-4 microns.
[0043] In some embodiments, preferably, the single crystal lithium-rich manganese-based positive electrode material includes a plurality of primary particles with an average particle size of 2.5-3 microns.
[0044] When the average particle size of the primary particles is less than 1 μm, the specific surface area is small, the electrolyte invades, resulting in many microcracks and invalid pores, low compaction density, and low volume energy density; when the average particle size of the primary particles is greater than 4 μm, Li + The diffusion channel is lengthened, which inhibits the Li + 's diffusion performance, thereby affecting the electrochemical performance of the battery. The primary particles of the positive electrode material provided by the present invention are relatively large in size. When the average particle size of the primary particles meets the above range, firstly, the specific surface area of the positive electrode material is reduced, which is beneficial to inhibit the performance attenuation caused by the infiltration of the electrolyte into the body of the positive electrode material; secondly, the primary particles in the obtained negative electrode are dispersed, which effectively alleviates the anisotropic volume deformation generated between the agglomerated primary particles, thereby reducing the risk of microcracks; finally, due to the reduction in specific surface area and the reduction in ineffective pores between particles, the compaction density of the positive electrode material is greatly improved, thereby improving the volume energy density of the positive electrode material. When the average particle size of the preferred primary particles is 2.5-3 microns, the improvement of the above performance is most significant.
[0045] In some embodiments, preferably, the compaction density of the single crystal lithium-rich manganese-based positive electrode material is 3.2-4 g / cm 3 .
[0046] In some embodiments, preferably, the compaction density of the single crystal lithium-rich manganese-based positive electrode material is 3.6-4 g / cm3 .
[0047] In the present invention, when the compaction density of the lithium-rich manganese-based positive electrode material does not meet the above range, such as when the compaction density is less than 3g / cm 3 When the active material particles and the conductive agent particles have pores between each other, it is not conducive to the conduction of ions and electrons; the compaction density is greater than 4g / cm 3 When the positive electrode material is rolled over, cracks will appear due to excessive rolling, which is not conducive to the battery cycle performance. The compaction density can be 3.2g / cm 3 , 3.3g / cm 3 , 3.3g / cm 3 、3.4g / cm 3 , 3.5g / cm 3 、3.6g / cm 3 、3.7g / cm 3 , 3.8g / cm, 3.9g / cm 3 , 4g / cm 3 Any value between any two numbers in .
[0048] In some embodiments, preferably, the single crystal lithium-rich manganese-based positive electrode material has a chemical composition represented by the following general formula: mLi2MnO3·(1-m)LiMO2, wherein M includes Ni, Mn and optionally Co, 0 <m<1。
[0049] A third aspect of the present invention is a positive electrode sheet for a lithium-ion battery, wherein the positive electrode sheet for a lithium-ion battery comprises the single-crystal lithium-rich manganese-based positive electrode material described in the second aspect of the present invention.
[0050] A fourth aspect of the present invention is a lithium ion battery, wherein the lithium ion battery comprises the lithium ion battery positive electrode sheet described in the third aspect of the present invention.
[0051] According to a particularly preferred embodiment of the present invention, the preparation method comprises: sintering the first part of the lithium source with the multinary precursor containing nickel and manganese for the first time to obtain an intermediate with a spinel structure, wherein the molar ratio of the first part of the lithium source to the multinary precursor containing nickel and manganese is 0.7-0.8:1;
[0052] Sintering the second portion of the lithium source and the spinel structure intermediate for a second time to obtain a single-crystal lithium-rich manganese-based positive electrode material, wherein the molar ratio of the second portion of the lithium source to the spinel structure intermediate is 0.8-0.9:1;
[0053] The molar ratio of the total amount of the first lithium source and the second lithium source to the nickel-manganese-containing multi-element precursor is 1.55-1.6:1;
[0054] The first sintering process includes: heating from room temperature to 540-560°C at a heating rate of 5-6°C / min, pre-sintering for 4-6h, heating to 935-950°C at a heating rate of 5-6°C / min, and sintering for 4-6h;
[0055] The second sintering process includes: heating from room temperature to 540-560°C at a heating rate of 5-6°C / min, pre-sintering for 4-6h, heating to 940-960°C at a heating rate of 5-6°C / min, and sintering for 11-13h.
[0056] The present invention will be described in detail below through examples. In the following examples and comparative examples, the morphology of the positive electrode material is measured using a scanning electron microscope model S-4800 of Hitachi Company;
[0057] The compacted density was measured using a micrometer screw.
[0058] The average particle size was measured using a laser particle size analyzer;
[0059] The composition of the cathode material was measured by inductively coupled plasma (ICP).
[0060] XRD: obtained by using Rigaku's D / MAX-2500 / pc test;
[0061] SEM: Scanning electron microscope (SEM) operated at 5 kV using Hitachi S-4800;
[0062] Raman spectroscopy: Thermo Fischer DXR, 532 nm laser;
[0063] The volumetric capacity, gravimetric capacity and cycle performance of the battery were measured using the Landian Test System (LAND CT 2001A) tester of Wuhan Landian Electronics Co., Ltd.
[0064] The raw materials used in the examples and comparative examples are all commercially available.
[0065] Preparation Example 1
[0066] Weigh NiSO4·6H2O, CoSO4·7H2O, and MnSO4·4H2O in a molar ratio of 0.1625:0.1625:0.675, add the three into 0.5 L of deionized water and stir until dissolved to obtain a precursor solution;
[0067] A 5L coprecipitation reactor is prepared, wherein the atmosphere in the reactor is argon, 1L of deionized water is pumped into the reactor, and then an ammonia solution with a concentration of 1 mol / L is introduced to form a bottom liquid with the deionized water, and the pH value of the bottom liquid is controlled to be 11 by controlling the amount of the ammonia solution introduced, and then the pumping of the ammonia solution is stopped;
[0068] The precursor solution, 4 mol / L NaOH solution and 1 mol / L ammonia solution were pumped into the reactor by a peristaltic pump, wherein the feed rates of the precursor solution and the NaOH solution were both 100 mL / h, and the pH value of the reaction system in the reactor was adjusted to 11 by regulating the feed rate of the ammonia solution. The reaction temperature of the reactor was controlled to be 55° C. by a water bath, and the reaction was stirred at a stirring rate of 1000 rpm. After the precursor solution was fed, it was aged for 12 hours to obtain a component of Ni 0.1625 Co 0.1625 Mn 0.675 The obtained nickel-manganese-containing multinary precursor of (OH)2 is vacuum dried at 80°C for 48 hours for later use.
[0069] Preparation Example 2
[0070] The method of Preparation Example 1 was followed except that NiSO4·6H2O, CoSO4·7H2O, and MnSO4·4H2O were weighed in a molar ratio of 0.2:0.1:0.7 to obtain Ni 0.2 Co 0.1 Mn 0.7 The obtained nickel-manganese-containing multinary precursor of (OH)2 is vacuum dried at 80°C for 48 hours for later use.
[0071] Preparation Example 3
[0072] The method of Preparation Example 1 was followed except that NiSO4·6H2O and MnSO4·4H2O were weighed at a molar ratio of 0.25:0.75 to obtain Ni 0.25 Mn 0.75 The obtained nickel-manganese-containing multinary precursor of (OH)2 is vacuum dried at 80°C for 48 hours for later use.
[0073] Example 1
[0074] (1) LiOH and Ni with a molar ratio of 0.8:1 0.1625 Co 0.1625 Mn 0.675(OH)2, after mixing at a rotation speed of 1500 rpm for 5 min, the temperature was increased from 30 °C to 550 °C at a heating rate of 5 °C / min, and after pre-sintering for 5 h, the temperature was increased to 935 °C at a heating rate of 5 °C / min and sintered for 5 h to obtain an intermediate with a spinel structure, which was recorded as L-SC-intermediate;
[0075] (2) After the L-SC-intermediate is cooled to room temperature, LiOH and L-SC-intermediate with a molar ratio of 0.8:1 are mixed at a rotation speed of 1500 rpm for 5 minutes, and then the temperature is increased from 30°C to 550°C at a heating rate of 5°C / min. After pre-sintering for 5 hours, the temperature is increased to 950°C at a heating rate of 5°C / min and sintered for 12 hours to obtain a single crystal lithium-rich manganese-based positive electrode material, which is recorded as L-SC.
[0076] The XRD pattern of L-SC obtained is shown in Figure 2 As shown in the second figure in the first row, it can be seen from the figure that L-SC has diffraction peaks at 2θ of 17°-18°, 36°-37°, 43°-45°, 48°-49°, 58°-59°, 64°-65°, 65°-66° and 68°-69°, that is, a layered phase, and a diffraction peak at 2θ of 20°-25°, that is, a lithium-rich phase.
[0077] Example 2
[0078] (1) Li2CO3 and Ni with a molar ratio of 0.2:1 0.2 Co 0.1 Mn 0.7 (OH)2, after mixing at a rotation speed of 1500 rpm for 5 min, the temperature was increased from 30°C to 580°C at a heating rate of 6°C / min, and after pre-sintering for 7 h, the temperature was increased to 950°C at a heating rate of 6°C / min and sintered for 6 h to obtain an intermediate with a spinel structure;
[0079] (2) After the spinel structure intermediate is cooled to room temperature, Li2CO3 and the intermediate with a molar ratio of 1.4:1 are mixed at a rotation speed of 1500 rpm for 5 minutes, and then the temperature is increased from 30°C to 580°C at a heating rate of 6°C / min. After pre-sintering for 7 hours, the temperature is increased to 935°C at a heating rate of 6°C / min and sintered for 14 hours to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0080] Example 3
[0081] (1) LiOH and Ni with a molar ratio of 0.6:1 0.25 Mn 0.75(OH)2, after mixing at a rotation speed of 1500 rpm for 5 minutes, the temperature was increased from 30°C to 620°C at a heating rate of 4°C / min, and after pre-sintering for 3 hours, the temperature was increased to 920°C at a heating rate of 4°C / min and sintered for 4 hours to obtain an intermediate with a spinel structure;
[0082] (2) After the spinel structure intermediate is cooled to room temperature, LiOH and the intermediate with a molar ratio of 1:1 are mixed at a rotation speed of 1500 rpm for 5 minutes, and then the temperature is increased from 30°C to 620°C at a heating rate of 4°C / min. After pre-sintering for 3 hours, the temperature is increased to 920°C at a heating rate of 4°C / min and sintered for 10 hours to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0083] Example 4
[0084] The process is carried out in the same manner as in Example 1, except that the heating rates of pre-sintering and sintering in step (1) are both 9° C. / min.
[0085] Example 5
[0086] The process is carried out in the same manner as in Example 1, except that the heating rates of pre-sintering and sintering in step (2) are both 9° C. / min.
[0087] Comparative Example 1
[0088] Weigh LiOH and Ni in a molar ratio of 1.6:1 0.1625 Co 0.1625 Mn 0.675 (OH)2, after mixing at a rotation speed of 1500rpm for 5min, the temperature was increased from 30℃ to 550℃ at a heating rate of 5℃ / min. After pre-sintering for 5h, the temperature was increased to 950℃ at a heating rate of 5℃ / min and sintered for 12h to obtain the positive electrode material, which was recorded as M-SC.
[0089] Comparative Example 2
[0090] Li(CH3COO2)·2H2O, Ni(CH3COO)2·4H2O, Co(CH3COO)2·4H2O and Mn(CH3COO)2·4H2O are weighed in a molar ratio of 1.25:0.13:0.13:0.54 respectively, mixed in 0.1 L of deionized water to obtain a metal salt solution, then citric acid in an equal molar ratio to the metal salt solution is weighed and dissolved in 0.1 L of deionized water to obtain a citric acid solution, the uniformly mixed citric acid solution is added dropwise to the metal salt solution to obtain a mixed solution, and an appropriate amount of ammonia solution is added to adjust the pH value of the mixed solution to 7, wherein the volume concentration of the ammonia solution is 12%, and the mixed solution is evaporated to a gel state under heating at 80°C in a water bath.
[0091] After the gel was taken out, it was placed in an oven at 80°C for vacuum drying for 48 hours, then heated from 30°C to 450°C at a heating rate of 5°C / min. After pre-sintering for 5 hours, it was heated to 900°C at a heating rate of 5°C / min and sintered for 12 hours to obtain the positive electrode material, which was recorded as S-SC.
[0092] Comparative Example 3
[0093] The method of Example 1 is followed, except that: in step (1), LiOH and Ni 0.1625 Co 0.1625 Mn 0.675 The molar ratio of (OH)2 is 0.05:1.
[0094] Comparative Example 4
[0095] The method of Example 1 is followed, except that: in step (1), LiOH and Ni 0.1625 Co 0.1625 Mn 0.675 The molar ratio of (OH)2 is 1.5:1.
[0096] Comparative Example 5
[0097] The process was carried out in the same manner as in Example 1, except that the molar ratio of LiOH to the intermediate in step (2) was 0.2:1.
[0098] Comparative Example 6
[0099] The process was carried out in the same manner as in Example 1, except that the molar ratio of LiOH to the intermediate in step (2) was 1.6:1.
[0100] Comparative Examples 7-11
[0101] The process was carried out in the same manner as in Example 1, except that in step (1), the temperature was increased to 550°C, 650°C, 750°C, and 850°C at a heating rate of 5°C / min and then sintered for 5h to obtain spinel structured intermediates, which were respectively denoted as D7-D11.
[0102] Test Example 1
[0103] The positive electrode materials obtained in the above Examples 1-5 are respectively recorded as A1-A5, and the positive electrode materials in Comparative Examples 1-6 are respectively recorded as D1-D6. The physical properties of A1-A5 and D1-D6 are tested, and the test items include: material composition, structural morphology, compaction density, and average particle size of primary particles.
[0104] In addition, the intermediates obtained from D7-D11 were respectively subjected to SEM scanning to observe the changes in the particle size of the intermediates.
[0105] Test Example 2
[0106] The negative electrode materials of the above Examples 1-5 and Comparative Examples 1-6 were assembled into lithium ion batteries, and the electrochemical performance tests were performed as follows:
[0107] (1) Weighing the positive electrode material, conductive agent (Super P), and binder (PVDF-polyvinylidene fluoride) in a mass ratio of 8:1:1, mixing them evenly, adding an appropriate amount of N-methylpyrrolidone (NMP) as a dispersant to prepare a slurry, coating it on aluminum foil, drying it, and cutting it into pieces to make a positive electrode sheet for a lithium-ion battery;
[0108] (2) The lithium-ion battery positive electrode prepared in step (1) is used, a metal lithium sheet is used as the negative electrode, a Celgard 2500 separator is used, and the main components of the electrolyte are 1 mol / L LiPF6 as the solute and a mixed liquid of dimethyl carbonate, diethyl carbonate, and ethylene carbonate in a volume ratio of 1:1:1 as the solvent, and button batteries are assembled in an argon atmosphere glove box.
[0109] The constant current charge and discharge test of the battery is carried out using the Landian test system (CT2001A LAND) tester of Wuhan Landian Electronics Co., Ltd. The test method is as follows:
[0110] The test was carried out in a 30°C constant temperature box, with a current rate of 0.1C (1C = 250mA) and charge and discharge tests in the voltage range of 2-4.8V.
[0111] The data analysis of the above tests is as follows:
[0112] Figure 1 These are SEM images of the L-SC intermediate obtained in step (1) of Example 1, the L-SC obtained in step (2), and the M-SC and S-SC prepared in Comparative Examples 1 and 2.
[0113] from Figure 1 It can be seen that the primary particle size of the L-SC-intermediate is about 2-3 microns. The primary particle size of the L-SC synthesized using the intermediate is basically consistent with that of the intermediate, which confirms the feasibility of this experimental method. Figure 1 It can also be seen that the primary particles of the prepared L-SC are independently dispersed and approximately spherical, without agglomeration into secondary particles, and are called "single crystals".
[0114] The primary particle size of M-SC synthesized by ordinary process is between 0.5-1 micron, which is significantly smaller than L-SC. This leads to a corresponding increase in the specific surface area and ineffective pores of M-SC materials, offsetting some advantages of single crystal morphology materials. The particle size of S-SC synthesized by sol-gel method is between 0.1-0.3 micron. Smaller grain size means more specific surface area and ineffective pores, which will reduce the volume energy density of the material on the one hand, and negatively affect the stability of the material on the other hand.
[0115] Figure 2 is a SEM image of the intermediates obtained in Example 1 and Comparative Examples 7-11. Specifically, Figure 2 The two pictures in the first row are SEM pictures of the intermediates with the first calcination temperature of 550℃ and 650℃ from left to right, the second picture in the second row are SEM pictures of the intermediates with the first calcination temperature of 750℃ and 850℃ from left to right, and the second row are SEM pictures of the intermediates with the first calcination temperature of 935℃.
[0116] from Figure 2 It can be seen that the average particle size of the intermediate obtained at different temperatures changes. When the temperature of the first sintering is 550-850℃, the average particle size of the intermediate obtained is small and there is no obvious change. When the temperature reaches 935℃, the average particle size of the intermediate obtained suddenly changes to 1-4 microns. The study found that when the temperature of the first sintering is not less than 880℃, this sudden change in average particle size can occur.
[0117] Figure 3 It is a schematic diagram of XRD of the L-SC intermediate obtained in step (1) of Example 1, the L-SC obtained in step (2), and the M-SC and S-SC prepared in Comparative Examples 1 and 2.
[0118] from Figure 3 It can be seen that the L-SC-intermediate material is a material with a space group of The spinel structure of L-SC, M-SC and S-SC is the space group of The composite structure of the layered structure and the lithium-rich structure. It is confirmed that the present invention utilizes that under the same conditions, the spinel structure has more identical (111) crystal planes and is more likely to promote the growth of grain size, thereby achieving a larger grain size than the layered phase. By utilizing the intermediate of the spinel structure, the synthesized L-SC positive electrode material has a grain size similar to that of its spinel structure intermediate. In comparison, the grain size of the layered material synthesized by other processes is significantly smaller.
[0119] Figure 4 It is the Raman spectrum of the L-SC intermediate and the positive electrode material L-SC obtained in Example 1.
[0120] from Figure 4 It can be seen that the L-SC-intermediate has the vibration signals of Ni-O and Mn-O bonds in the spinel structure, while L-SC has the typical vibration signals of the layered structure.
[0121] Figure 5 It is a schematic diagram of the weight specific capacity of the positive electrode materials prepared in Example 1 and Comparative Examples 1 and 2.
[0122] from Figure 5 It can be seen that L-SC has a relatively low weight specific capacity, while M-SC has a medium weight specific capacity, and S-SC has the highest weight specific capacity. This is because the kinetic performance of the LMR material itself is relatively poor, and its kinetic performance is more affected by the particle size. Therefore, as the particle size increases, the kinetic performance is inversely proportional, which further leads to the inverse proportional performance of its first-week specific capacity.
[0123] Figure 6 It is a schematic diagram of the volume specific capacity of the positive electrode materials prepared in Example 1 and Comparative Examples 1 and 2.
[0124] from Figure 6 It can be seen that L-SC has the highest volumetric capacity, M-SC has a medium volumetric capacity, and S-SC has the lowest weight capacity. This is because the larger the particle size of the material, the smaller the ineffective pores and specific surface area between the particles. After roller pressing, it can often achieve a higher compaction density, which further leads to a higher specific capacity of the material at the same volume. As the particle size of the material increases, the volumetric capacity is usually proportional to it.
[0125] Figure 7 It is a schematic diagram of the 100-cycle capacity retention rate of the positive electrode materials prepared in Example 1 and Comparative Examples 1 and 2.
[0126] from Figure 7 It can be seen that L-SC has the best capacity retention rate, and after 100 cycles, the capacity retention rate reached 97.95%, M-SC has a medium capacity retention rate, and after 100 cycles, the capacity retention rate reached 71.96%, and S-SC has the worst capacity retention rate, and after 100 cycles, the capacity retention rate was only 64.86%. This is because the larger the particle size, the smaller the specific surface area, and the smaller the chance of the electrolyte reacting with the material and immersing in the bulk phase of the material, thus achieving higher stability. On the other hand, the larger the material, the smaller the degree of anisotropic volume deformation between its primary particles, which will further improve its capacity retention rate while maintaining the stability of the material structure during the cycle.
[0127] The positive electrode materials obtained in each of Examples 1-5 and Comparative Examples 1-6 include a layered phase and a lithium-rich phase, and the specific physicochemical parameter test results are shown in Table 1.
[0128] Table 1 Physical and chemical parameter test results
[0129]
[0130] Table 2 0.1C electrochemical performance test results
[0131]
[0132]
[0133] It can be seen from Table 1 and Table 2 that the first-cycle discharge specific capacity and the first-cycle volume specific capacity of the positive electrode material prepared by the present invention are both relatively high, especially the capacity retention rate after 100 cycles is not less than 92%.
[0134] It can be seen from Example 3 that due to the large particle size and lack of Co, the material kinetics is poor, and some Li ions cannot be embedded or released in the first few weeks of the cycle, resulting in low capacity. In the subsequent 10-20 weeks, the Li ions are continuously activated, resulting in a gradual increase in capacity, and then stabilized at a certain capacity (maintained at about 190 mAh / g). Therefore, compared with the first week of cycling, the capacity retention rate exceeds 100% after 100 cycles.
[0135] It can be seen from Examples 1, 4 and 5 that when the heating rate is too high, the various directional properties of the positive electrode material under braking are reduced.
[0136] It can be seen from Example 1 and Comparative Examples 1 and 2 that the step-by-step method provided by the present invention can effectively improve the first-cycle coulomb efficiency and the capacity retention rate of the positive electrode material after 100 cycles of braking, compared with the one-step method and the traditional gel method.
[0137] It can be seen from Example 1 and Comparative Examples 3-6 that when the molar ratio of the lithium source to the precursor or the lithium source to the intermediate is lower than or higher than a certain range, the anisotropic properties of the obtained positive electrode material are poor. It can be seen that the size of the primary particles of the positive electrode material obtained by the method provided by the present invention is larger, so that the positive electrode material has excellent structural stability, and the lithium ion battery made from the positive electrode material has excellent volumetric capacity and cycle stability.
[0138] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a single-crystal lithium-rich manganese-based positive electrode material, characterized in that: The preparation method comprises: Sintering the first part of the lithium source and the nickel-manganese-containing multinary precursor for the first time to obtain an intermediate with a spinel structure, wherein the molar ratio of the first part of the lithium source to the nickel-manganese-containing multinary precursor is 0.2-1:1; Sintering the second portion of the lithium source and the spinel structure intermediate for a second time to obtain a single-crystal lithium-rich manganese-based positive electrode material, wherein the molar ratio of the second portion of the lithium source to the spinel structure intermediate is 0.5-1.4:1; The molar ratio of the total amount of the first lithium source and the second lithium source to the nickel-manganese-containing multi-element precursor is greater than 1.
25.
2. The preparation method according to claim 1, wherein The first sintering process includes: heating from room temperature to 500-650°C at a heating rate of 3-7°C / min, pre-sintering for 2-8h, and then heating to 880-980°C at a heating rate of 3-7°C / min, and sintering for 2-8h; Preferably, the first sintering process comprises: heating from room temperature to 550-620°C at a heating rate of 4-6°C / min, pre-sintering for 3-7h, heating to 920-950°C at a heating rate of 4-6°C / min, and sintering for 4-6h.
3. The preparation method according to claim 1 or 2, wherein The second sintering process includes: heating from room temperature to 500-650°C at a heating rate of 3-7°C / min, pre-sintering for 2-8h, then heating to 920-980°C at a heating rate of 3-7°C / min, and sintering for 8-15h; Preferably, the second sintering process comprises: heating from room temperature to 550-620°C at a heating rate of 4-6°C / min, pre-sintering for 3-7h, heating to 920-950°C at a heating rate of 4-6°C / min, and sintering for 10-14h.
4. The preparation method according to any one of claims 1 to 3, wherein The lithium source is selected from LiOH and / or Li2CO3.
5. The preparation method according to any one of claims 1 to 4, wherein: The general formula of the nickel-manganese-containing multi-element precursor is: Ni x Co y Mn z (OH)2, where 0.15≤x≤0.3, 0≤y≤0.2, 0.5≤z≤0.8; Preferably, the nickel-manganese-containing multinary precursor is selected from Ni 0.25 Mn 0.75 (OH)2、Ni 0.2 Co 0.1 Mn 0.7 (OH)2 and Ni 0.1625 Co 0.1625 Mn 0.675 At least one of (OH)2.
6. A single crystal lithium-rich manganese-based positive electrode material prepared according to the preparation method according to any one of claims 1 to 5, characterized in that: The single crystal lithium-rich manganese-based positive electrode material includes a layered phase and a lithium-rich phase. The single crystal lithium-rich manganese-based positive electrode material includes a plurality of primary particles with an average particle size of 1-4 microns, preferably primary particles with an average particle size of 2.5-3 microns.
7. The single crystal lithium-rich manganese-based positive electrode material according to claim 6, wherein: The compaction density of the single crystal lithium-rich manganese-based positive electrode material is 3.2-4 g / cm 3 , preferably 3.6-4g / cm 3 .
8. The single crystal lithium-rich manganese-based positive electrode material according to claim 6 or 7, wherein: The single crystal lithium-rich manganese-based positive electrode material has a chemical composition represented by the following general formula: mLi2MnO3·(1-m)LiMO2, wherein M includes Ni, Mn and optionally Co, 0 <m<1。 9. A positive electrode sheet for a lithium-ion battery, characterized in that: The lithium-ion battery positive electrode sheet comprises the single-crystal lithium-rich manganese-based positive electrode material according to any one of claims 6 to 8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Preparation method of large monocrystalline layered cathode material used for lithium ion battery
CN106910882A
Improved preparation method of large single crystal layered positive electrode material for lithium ion battery
CN107311242A
Preparation process of high-voltage single-crystal positive electrode material of lithium ion battery
CN115385391A
Monocrystal lithium-rich material, preparation method thereof and energy storage device
CN116856058A
Cited By
Lithium-rich manganese-based positive electrode material with bulk phase containing spinel structure, preparation method of lithium-rich manganese-based positive electrode material and lithium ion battery
CN120453363A
A lithium-rich manganese-based positive electrode material containing a spinel structure in a bulk phase and a preparation method thereof, and a lithium ion battery
CN120453363B
Monocrystal cobalt-free lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
CN121317905A
Multinary material, cathode material, and battery
CN122809546A